1999
DOI: 10.1029/1999gl900456
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric mass ejection in response to a CME

Abstract: Abstract. We report observations of a direct ionospheric plasma outflow response to the incidence of an interplanetary shock and associated coronal mass ejection (CME) upon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(171 citation statements)
references
References 9 publications
12
159
0
Order By: Relevance
“…Because of their heavier mass, oxygen ions carry more energy per unit number density than protons. The enhanced ionospheric outflow during storms (e.g., Moore et al, 1999) enriches the O + content in the plasma sheet, and this stormtime variation is clearly seen in composition measurements (e.g., Young et al, 1982;Lennartsson and Shelley, 1986;Nose et al, 2001;Fu et al, 2001;Pulkkinen et al, 2001). However, these studies show substantial scatter about the mean trends.…”
Section: Ring Current Inputmentioning
confidence: 46%
“…Because of their heavier mass, oxygen ions carry more energy per unit number density than protons. The enhanced ionospheric outflow during storms (e.g., Moore et al, 1999) enriches the O + content in the plasma sheet, and this stormtime variation is clearly seen in composition measurements (e.g., Young et al, 1982;Lennartsson and Shelley, 1986;Nose et al, 2001;Fu et al, 2001;Pulkkinen et al, 2001). However, these studies show substantial scatter about the mean trends.…”
Section: Ring Current Inputmentioning
confidence: 46%
“…That interpretation is also consistent with the locally enhanced O + flow density in the cusp regions of Figure 1, and it meshes quite well, in fact, with earlier reports on the outflow of O + ions with energies below 15 eV, since the rate of outflow of so-called ''suprathermal'' O + ions has been found to be especially strong in the cusp regions (''ion fountains'' [Lockwood et al, 1985]) and rather well correlated with the solar wind dynamic pressure, especially with its standard deviation, more so than with several other solar wind parameters [e.g., Moore et al, 1999;Elliott et al, 2001;Cully et al, 2003]. In terms of solar wind power input it might seem then that the kinetic energy flow density K ought to be especially important, a conjecture that can indeed be drawn from the comparison of K and S in Figures 4 and 5 as well.…”
Section: Discussionmentioning
confidence: 89%
“…[19] Since the peak upwelling, 10-eV type O + flux, on the dayside, is known to be better correlated with the preceding hourly standard deviation of a solar wind parameter, such as dynamic pressure (time shifted to Earth), than with the hourly mean parameter itself [Moore et al, 1999;Pollock et al, 1990]; it is probably preferable to compare our 12-and 24-s samplings with solar wind averages that are shorter than an hour. Using the $2-min Wind key parameters [Ogilvie et al, 1995;Lepping et al, 1995] individually, on the other hand, is most likely less than optimal, because the observed ion outflows at Polar may represent longer travel times than that from the source, ranging from a few seconds to several minutes at perigee, with low-energy O + ions being the slowest.…”
Section: Solar Wind Power Inputmentioning
confidence: 99%
“…[46] It has often been observed that powerful ionospheric escape events, referred to as ionospheric mass ejections [Moore et al, 1999], often contain appreciable amounts of the molecular ions N 2 + and NO + . Wilson and Craven [1999] showed that such events were associated with strong and prolonged (>15 min) convection of the ionosphere.…”
Section: Discussionmentioning
confidence: 99%